METODE PENAFSIRAN BUYA HAMKA DALAM TAFSIR AL-AZHAR - Alfiyah, Avif (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
Buya HAMKA, a prominent Indonesian Muslim leader, poet, author, historian, and educator, was so instrumental to Indonesian scientific development, especially for the world of Islam in Indonesia. The greatest work of him is his commentary entitled Tafsir al-Azhar. This article explains about the methodology of HAMKAâs interpretation on Qurâanic verses. In the conclusion, Tafsir al-Azhar can be classified as tafsÃ®r bi al-maâtsÃ»r based on it source, with tahlÃ®lÃ® method because it is begun from Surah al-FÃ¢tihah until Surah al-NÃ¢s, muqÃ¢rin method for its explanation, and categorized as tafsÃ®r tafshÃ®lÃ® too according to his width exploration in the tafsir. While the feature of his tafsir is dominated by adÃ¢bÃ® ijtimÃ¢âÃ® with the beauty of Malayan language related to the social reality in his era. After all, his tafsir is being easy to understand for Indonesian people as the majority reader of it.Â